Applications of Artificial Intelligence In Construction Industry - Tan, Daniel Chee Feng (2021)
With the rising complexity of the construction industry's problems, researchers are exploring and investigating computationally rigorous intelligent systems to seek intelligent solutions. Therefore, this research study was performed to investigate the applications, issues and challenges of A.I. systems in the construction industry. The objectives are to explore the application of A.I. in the construction industry; to identify the challenges and issues of A.I. in the construction industry, and to propose the future development of A.I. in the industry. The qualitative research method was adopted in this research. Literature related to A.I. in construction has been reviewed to develop a theoretical framework for this research. Furthermore, the SWOT analysis was conducted to assess the possible issues and challenges of A.I. encountered in the construction field. The findings revealed the four challenges of adopting A.I. systems, which are: (1) Legal issues and regulatory challenge, (2) Human labour, (3) Privacy, and (4) Ethical. This study has also incorporated the A.I. FourDimensional Model, including the technical, policy, process and social dimensions. Although A.I. technology is widespread in most parallel industries, construction is the slowest vertical in terms of adopting the technology. At the end of this research, the possible future development of A.I. in the construction industry is proposed. It is expected that automation will gradually replace the current labour workers in the future to improve productivity and efficiency. Moreover, rising material and skilled labour costs will cause organisations to automate more and take advantage of machines over humans.